Implementasi dan Kontribusi KKN Dalam Pembelajaran Keagamaan di MDTA Desa Hariang - Muslihah Amalia Qurotaayun; Sri Mulyanni; Muhamad Andri; Muhamad Rafi Aulia; Halmi Abdul Halim (Penerbit Lestari Sakha Pustaka, 2026)
Community Service Program (Kuliah Kerja Nyata/KKN) is a form of student community engagement aimed at applying academic knowledge, skills, and values in real social contexts. One of the main focuses of the KKN Community Service Program (PKM) in Hariang Village is the strengthening of religious learning at Madrasah Diniyah Takmiliyah Awaliyah (MDTA) as a nonformal Islamic educational institution that plays an important role in shaping the character and moral values of the younger generation. This program was implemented through learning assistance in Al-Qur’an studies, fiqh of worship, aqidah, and akhlak by applying creative, innovative, and participatory learning methods that are tailored to the characteristics of the students. The implementation of the KKN program showed positive results, as indicated by an increase in students’ learning motivation, improved understanding of religious materials, and the development of religious attitudes and noble character (akhlakul karimah) in daily life. In addition, the presence of KKN students provided support for MDTA teachers in developing more varied, engaging, and effective learning methods. Thus, the KKN program made a tangible contribution to improving the quality of nonformal religious education in Hariang Village. This article positions the KKN activities as a form of community-based empowerment using the Participatory Action Research (PAR) approach, which emphasizes active collaboration among students, MDTA teachers, students, and the local community in the processes of planning, implementation, and continuous evaluation.